2013
DOI: 10.1590/s0104-64972013000200010
|View full text |Cite
|
Sign up to set email alerts
|

A case of malformation on the third maxilliped of Uca rapax (Smith, 1870) (Decapoda: Ocypodidae)

Abstract: -This paper evaluates the malformation in the left third maxilliped of a specimen of the fiddler crab Uca rapax from Venezuela. There are some hypotheses and the cause of the malformation remains unknown, but the results are indicative that is most likely due to errors in morphogenetic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nauplius, 26: e2018032 recorded cheliped malformation in a specimen of Ucides cordatus (Linnaeus, 1763), Fransozo et al (2012) described external morphological abnormalities in marine crabs (Decapoda, Brachyura) on the northern coast of the state of São Paulo, and Lira et al (2013) recorded a case of malformation in the third maxilliped for a fiddler crab violinist Uca rapax [= Minuca rapax (Smith, 1870)]. Recently, Zambrano (2017) recorded the first case of malformation in Ucides occidentalis (Ortmann, 1897) for 11 specimens in the Gulf of Guayaquil, Ecuador.…”
Section: Bilateral Hypertrophy In Chelae Of Minuca Rapaxmentioning
confidence: 99%
See 1 more Smart Citation
“…Nauplius, 26: e2018032 recorded cheliped malformation in a specimen of Ucides cordatus (Linnaeus, 1763), Fransozo et al (2012) described external morphological abnormalities in marine crabs (Decapoda, Brachyura) on the northern coast of the state of São Paulo, and Lira et al (2013) recorded a case of malformation in the third maxilliped for a fiddler crab violinist Uca rapax [= Minuca rapax (Smith, 1870)]. Recently, Zambrano (2017) recorded the first case of malformation in Ucides occidentalis (Ortmann, 1897) for 11 specimens in the Gulf of Guayaquil, Ecuador.…”
Section: Bilateral Hypertrophy In Chelae Of Minuca Rapaxmentioning
confidence: 99%
“…Fransozo et al (2012) argued that some malformation in decapods can been attributed to a double generation of growth areas. Lira et al (2013) suggested that malformation of the third maxilliped in Uca rapax (= M. rapax) occurs due to errors in morphogenetic processes; Vale et al (2015) analyzed the hypertrophy of chelipeds in U. rapax (= M. rapax) and stated that the collected specimen may have suffered a dysfunction of the androgenic gland, which altered the development of sexual characteristics (Tab. 2).…”
Section: Bilateral Hypertrophy In Chelae Of Minuca Rapaxmentioning
confidence: 99%